(untitled) (European Bison Conservation Newsletter, 2019)
The paper presents information regarding the conservation and a study on European bison biology in natural habitat of the north of the European part of Russia. Particular attention is paid to the successful acclimatization of the species in the new habitat conditions. The paper identifies the main free-breeding European bison populations within the Russian Federation. The issues of further preservation and improvement of free-breeding populations, the direction of future studies on those animals considering the performance of the species in contemporary habitat conditions are discussed.